ANALISIS MARJIN PEMASARAN KEMIRI DI KECAMATAN KABOLA KABUPATEN ALOR - Ferdinan Demang (Politeknik Pertanian Negeri Kupang, 2018)
Analysis of Marketing Margin of Pecan in Kabola District of Alor Regency This study aimed to analyze the marketing channel of candlenut, the magnitude of the marketing margin of candlenut and the distribution of marketing margins of candlenut in the District of KabolaAlor Regency The method used in this study was primary and secondary data. Primary data is obtained through interviews with informants who know the development of candlenuts (qualitative). While secondary data is obtained from several agencies that are used to determine the development of candlenuts. Analyzing the factors that influence marketing margins carried out by direct observation, interviews with data collection of primary data and secondary data, informal as many as 56 people quantitatively From the results of the study it is known that in the first marketing channel the average marketing margin is the price difference at the consumer level and farmers are Rp.5,020.24/kg. The average price at the retailer level is Rp.21,186.90/kg and the average price of the farmer level is (Rp. 16,166.67/kg).It can be seen that the marketing margin ranges from Rp.4,500/kg to Rp.5,150/kg with the price range at the retailer level is Rp.16,100/kg up to Rp.24,000/kg and the price range at the farmer level is Rp.11,000/kg up to Rp.19,000/kg. There are variations in prices in every marketing agencybecause each marketing agency spends different marketing costs so the price is different. In the marketing process both the average marketing margin at the consumer level and the farmer level is Rp.4,321.43/kg. This margin is the average difference in the selling price of retailers as much asRp.22,607.14/kg and the average level of farmers is Rp.18,285.71/kg.